Antecedents of Technology Selection for Project Use. Issue 5 (3rd September 2021) - Cuellar, Michael J.; Tabatabaei, Manoucheher; Case, Thomas
ABSTRACT: The adoption and use of technology have been an important topic of research in Information Systems. However, projects create a different environment for technology adoption in that they are temporary organizations which are formed specifically for the project and then disbanded as opposed to the continuing organizations which have been traditionally studied. We term this adoption and use in temporary organizations as project use . The purpose of this study is to examine how previous experience with a technology in a project affects the selection of that technology within subsequent projects. The findings support Technology Continuation Theory as a partial explanation for project use but the key factors for project use are different from those in continuing organizations. Project use seems to be a much more pragmatic than hedonic decision. The question "does it work satisfactorily?" seems to be more important than "is it easy or pleasant to use?"